(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
In the last decade a substantial number of epidemiological studies suggested that outdoor air pollution and in particular respirable particulate matter (PM10) and fine particulate matter (PM2.5) are associated with an increased risk of lung cancer. The most recent is a multicentre European study...